The Ills of Legal Education - Zile, Zigurds (1980)
This article offers a critical view of university legal education, highlighting the identity and purpose crisis it faces. In this context, the author identifies three main issues: the fundamental objectives, the quality of students, and the pedagogical process. In this regard, he argues that legal education should not be limited to training lawyers since law is a multifaceted discipline and, as lawyers handle conflicts in a confrontational context, they must have skills that go beyond the application of rules, such as the perception of facts, the recognition of values and interests and the analysis of problems. The text also criticizes law school admissions methods, which focus on specific skills rather than maturity and life experience. In addition it questions teaching methods centered on legal liturgy, proposing problem analysis as a more effective pedagogical alternative. Thus, it is suggested that legal education should include instruction in practical skills and exposure to the ambiguity and flexibility of law, preparing students for social changes and evolving legal rules. Consequently, the author proposes a reform to develop professionals with a deep understanding of human conflicts, the ability to analyze and communicate effectively, and an appreciation of the complexity and ambiguity of law, which are essential for professional practice and service to society.